ANNOTATED CHECKLIST OF CYRTANDRA (GESNERIACEAE) OF SUMATRA, INDONESIA - Qing Wen Wang; Gemma L.C. Bramley; Hannah J. Atkins; Abdulrokhman Kartonegoro (BRIN Publishing (Penerbit BRIN), 2022)
WANG, Q. W., BRAMLEY, G. L. C., ATKINS, H. J. & KARTONEGORO, A. 2022. Annotated checklist of Cyrtandra (Gesneriaceae) of Sumatra, Indonesia. Reinwardtia 21(2): 63‒80. — There are 53 species and three varieties of Sumatran Cyrtandra (Gesneriaceae) included in the checklist. Thirty-three lectotypes and four neotypes have been assigned, including for two excluded species. Two species are designated as incertae sedis due to a lack of type material or any associated specimens. A new name of C. jackii is proposed here to replace the illegitimate C. glabra Jack. Most of the species included in the checklist are endemic to Sumatra, with some species distributed in neighboring islands in Malesia. The next step for Cyrtandra in Sumatra is to carry out a full taxonomic revision to better understand distribution patterns and species limits and also to assign appropriate neotypes for those species still missing original material.